Lipase activity sensitive to dopamine, Glucagon and cyclic amp in the Hepatopancreas of the Euryhaline burrowing crab Neohelice Granulata (Dana, 1851) (Decapoda, Grapsidae) - Lopez Mañanes, Alejandra Antonia (2015)
We studied the biochemical characteristics and modulation by dopamine, glucagon and cAMP of lipase activity in hepatopancreas of the euryhaline crab Neohelice granulata (Dana, 1851), considered to be an emergent model for biochemical, physiological and ecological research. Lipase activity was maximum at pH 8.5; it exhibited Michaelis-Menten kinetics (apparent Km = 0.018 mM), was highest at 37°C but appeared to be cold- and heat-tolerant, since it was high at 4°C and at 45°C. Lipase activity was enhanced upon incubation of hepatopancreas with 10?4 M dopamine (about 100%), 2 × 10?3 M glucagon (about 250%) and 10?4 M cAMP (about 150%) suggesting a role of these chemical messengers in mechanisms of regulation of lipolytic activities and its direct effect on the hepatopancreas. The concomitant decrease in triglycerides content upon dopamine and cAMP treatment suggests a link between enhanced lipase activity by these messengers and triglycerides catabolism.